Acute regulation of multidrug resistance-associated protein 2 localization and activity by cAMP and estradiol-17β-D-glucuronide in rat intestine and Caco-2 cells - Tocchetti, Guillermo Nicolás; Rigalli, Juan Pablo (Archives of toxicology, 2018)
Multidrug resistance-associated protein 2 (MRP2) is an ATP-dependent transporter expressed at the brush border membrane of the enterocyte that confers protection against absorption of toxicants from foods or bile. Acute, short-term regulation of intestinal MRP2 activity involving changes in its apical membrane localization was poorly explored. We evaluated the effects of dibutyryl-cAMP (db-cAMP), a permeable analog of cAMP, and estradiol-17β-d-glucuronide (E217G), an endogenous derivative of estradiol, on MRP2 localization and activity using isolated rat intestinal sacs and Caco-2 cells, a model of human intestinal epithelium. Changes in MRP2 localization were studied by Western blotting of plasma membrane (PM) vs. intracellular membrane (IM) fractions in both experimental models, and additionally, by confocal microscopy in Caco-2 cells. After 30 min of exposure, db-cAMP-stimulated sorting of MRP2 from IM to PM both in rat jejunum and Caco-2 cells at 10 and 100 µM concentrations, respectively, with increased excretion of the model substrate 2,4-dinitrophenyl-S-glutathione. In contrast, E217G (400 µM) induced internalization of MRP2 together with impairment of transport activity. Confocal microscopy analysis performed in Caco-2 cells confirmed Western blot results. In the particular case of E217G, MRP2 exhibited an unusual pattern of staining compatible with endocytic vesiculation. Use of selective inhibitors demonstrated the participation of cAMP-dependent protein kinase and classic calcium-dependent protein kinase C in db-cAMP and E217G effects, respectively. We conclude that localization of MRP2 in intestine may be subjected to a dynamic equilibrium between plasma membrane and intracellular domains, thus allowing for rapid regulation of MRP2 function.
Published online: 20 October 2017
Gesehen am 25.06.2018